Human Immunodeficiency Virus-Infected Women Have High Numbers of CD103−CD8+ T Cells Residing Close to the Basal Membrane of the Ectocervical Epithelium. (20th December 2017) - Gibbs, Anna; Buggert, Marcus; Edfeldt, Gabriella; Ranefall, Petter; Introini, Andrea; Cheuk, Stanley; Martini, Elisa; Eidsmo, Liv; Ball, Terry B; Kimani, Joshua; Kaul, Rupert; Karlsson, Annika C; et al.
Abstract : Tissue-resident memory (TRM ) cells defend tissue barriers against infections. Here, we provide insight into the distribution of CD8 + TRM cells in the genital mucosa of healthy and HIV-infected women; the main entry portal and initial replication site of HIV. Abstract: Background: Genital mucosa is the main portal of entry for various incoming pathogens, including human immunodeficiency virus (HIV), hence it is an important site for host immune defenses. Tissue-resident memory T (TRM ) cells defend tissue barriers against infections and are characterized by expression of CD103 and CD69. In this study, we describe the composition of CD8 + TRM cells in the ectocervix of healthy and HIV-infected women. Methods: Study samples were collected from healthy Swedish and Kenyan HIV-infected and uninfected women. Customized computerized image-based in situ analysis was developed to assess the ectocervical biopsies. Genital mucosa and blood samples were assessed by flow cytometry. Results: Although the ectocervical epithelium of healthy women was populated with bona fide CD8 + TRM cells (CD103 + CD69 + ), women infected with HIV displayed a high frequency of CD103 − CD8 + cells residing close to their epithelial basal membrane. Accumulation of CD103 − CD8 + cells was associated with chemokine expression in the ectocervix and HIV viral load. CD103 + CD8 + and CD103 − CD8 + T cells expressed cytotoxic effector molecules in the ectocervical epithelium of healthy and HIV-infected women. In addition, women infected with HIV had decreased frequencies of circulating CD103 + CD8 + T cells. Conclusions: Our data provide insight into the distribution of CD8 + TRM cells in human genital mucosa, a critically important location for immune defense against pathogens, including HIV.